Optimization of Source-Based Waste Management in Apuan Village Through Village Regulations - Luh Putu Suryani; Ni Made Puspasutari Ujianti; Ida Ayu Putu Widiati; I Made Gianyar; Dewa Gede Agung Semarabawa; I Wayan Sunarta; Ayu Metta Sandra; Ni Putu Laksmi Krisnina Maharani (Law Doctoral Community Service Journal, 2023)
Trash is a problem faced almost everywhere in the world. Considering the numerous waste issues that occur, it is expected that all elements of society work together to tackle the waste problem from upstream to downstream. Bali, which is famous as a tourist destination, also has serious waste issues, prompting the Governor of Bali to issue Governor Regulation No. 47 of 2019 regarding Source-Based Waste Management. The purpose of this research is also to discuss the legal framework that enables the Apuan village government to implement a source-based waste management program and to understand the mechanism of source-based waste management. The research method involves conducting interviews with the Apuan Village Government, Susut Sub-district, Bangli Regency. Source-based waste management has not been fully implemented in Apuan Village due to the lack of legal framework for source-based waste management. The proposed solution to the partner is to draft a new village regulation that provides detailed provisions for implementing source-based waste management, as well as conducting Focus Group Discussions (FGD) and raising awareness about the importance of proper waste management. The method to be used involves providing assistance during the drafting of the village regulation and conducting public awareness campaigns on the significance of source-based waste management.